2009
DOI: 10.1101/gad.1783809
|View full text |Cite
|
Sign up to set email alerts
|

The Rho-linked mental retardation protein oligophrenin-1 controls synapse maturation and plasticity by stabilizing AMPA receptors

Abstract: Oligophrenin-1 (OPHN1) encodes a Rho-GTPase-activating protein (Rho-GAP) whose loss of function has been associated with X-linked mental retardation (MR). The pathophysiological role of OPHN1, however, remains poorly understood. Here we show that OPHN1 through its Rho-GAP activity plays a critical role in the activitydependent maturation and plasticity of excitatory synapses by controlling their structural and functional stability. Synaptic activity through NMDA receptor activation drives OPHN1 into dendritic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
107
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(110 citation statements)
references
References 51 publications
3
107
0
Order By: Relevance
“…Again, this may not have functional significance, but could be an epiphenomenon arising from interaction between 'synaptic' oligophrenin-1 and 'nuclear' Rev-erbα. It is known that the oligophrenin-1 localization to dentritic spines is driven by synaptic activity where it complexes with, stabilizes, and selectively activates AMPA receptors 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Again, this may not have functional significance, but could be an epiphenomenon arising from interaction between 'synaptic' oligophrenin-1 and 'nuclear' Rev-erbα. It is known that the oligophrenin-1 localization to dentritic spines is driven by synaptic activity where it complexes with, stabilizes, and selectively activates AMPA receptors 39 .…”
Section: Discussionmentioning
confidence: 99%
“…First, based on previous reports demonstrating that mutations in the Ophn1 gene were associated with alterations in a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acidreceptor (AMPAR) trafficking [13,14], a process which depends on AMPAR phosphorylation [23], we tested the phosphorylation state of AMPARs in Ophn1 þ/y and Ophn1 2/y brain extracts using specific antibodies against phosphorylated forms of AMPARs [24] (see electronic supplementary material, figure S1c). We first observed that, even though the total amount of the AMPAR subunits GluA1 and GluA2 was similar in both genotypes (data not shown), PKA-mediated phosphorylation of AMPARs was higher in Ophn1 2/y brains, when compared with WT animals.…”
Section: Resultsmentioning
confidence: 99%
“…In hippocampal slice preparations, acute downregulation of ophn1 expression using siRNA approaches leads to alterations in the density and morphology of postsynaptic spine density along with changes in AMPARs mobility and deficits in postsynaptic LTP [14]. Consistent with these results and with the fact that dendritic spine morphology is affected in several genetic mouse models for X-linked intellectual disabilities (ID), including Il1rapl1 and Ophn1 [9,54], this suggests an important role for deficits in postsynaptic function and plasticity in the pathophysiology of X-linked ID.…”
Section: Discussionmentioning
confidence: 99%
“…tual disorders (25)(26)(27). Therefore, these studies highlight the importance of GEFs and GAPs in regulating spine and synapse function and point to a need to investigate the contribution of other GEFs and GAPs to these processes.…”
mentioning
confidence: 93%